Acute Diarrhea Patients among Children Under Five Hospitalized in a Tertiary Hospital in East Java, Indonesia - Asmahan Farah Adiba; Subijanto Marto Soedarmo; Sulistiawati Sulistiawati; Alpha Fardah Athiyyah (Folia Medica Indonesiana, 2022)
Highlight: • The characteristics of acute diarrhea patients among chidren in Tertiary Hospital In East Java was evaluated.